1997
DOI: 10.1007/bf00433986
|View full text |Cite
|
Sign up to set email alerts
|

Do we underestimate the predictive value of the ulnar styloid affection in Colles fractures?

Abstract: Various radiographic factors have been suggested as predictively important when dealing with an unstable distal radius fracture. Accordingly, many classification systems have been established in order to give an accurate description of a fracture and to grade the seriousness of the injury. In this paper, we use the classification of Colles fractures introduced by Frykman to investigate the predictive value of a concomitant fracture of the ulnar styloid. We found styloid affection to be a better predictor of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 16 publications
2
24
0
2
Order By: Relevance
“…Ulnar styloid fractures accompany 51% to 65% of distal radius fractures and represent important factor that may affect outcome. 7,[10][11][12] However, there is a controversy regarding the management of ulnar styloid process in distal radius fractures and the concept is highly debated. In this study all patients with distal radius fracture with or without ulnar styloid fracture were managed conservatively and the functional status was compared and statistically evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ulnar styloid fractures accompany 51% to 65% of distal radius fractures and represent important factor that may affect outcome. 7,[10][11][12] However, there is a controversy regarding the management of ulnar styloid process in distal radius fractures and the concept is highly debated. In this study all patients with distal radius fracture with or without ulnar styloid fracture were managed conservatively and the functional status was compared and statistically evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its close association with the TFCC, fractures of the ulnar styloid might indicate possible TFCC disruption and resultant DRUJ instability. Oskarsson et al 7 in a case series of 158 fractures found great degree of loss of mobility and grip strength in patients with styloid process fracture treated none surgically and concluded that styloid process to be great predictor of fracture instability than articular involvement. Stoffelen et al 8 also found that presence of a styloid fracture was associated with worse outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors associated with this injury, however, rarely have been studied. Because of its anatomic proximity to the triangular fibrocartilage complex, fracture of the ulnar styloid at its base has been postulated to cause DRUJ instability [12,28,33,37]. However, well-designed studies consistently denied the association between symptomatic DRUJ instability and the ulnar styloid fracture in distal radius fractures [15,35,39,44].…”
Section: Discussionmentioning
confidence: 99%
“…La irreductibilidad de la 66 . El diagnósti-co, en estos casos, depende del examen físico y de los hallazgos en la radiografía simple [67][68][69] . En casos de fracturas de la estiloides cubital, que afecten a más del 50% de la longitud de la apófisis estiloides y/o su desplazamiento mayor a 2 mm, asociadas a fracturas del radio distal, el riesgo de inestabilidad de la ARCD se encuentra aumentado 70 .…”
Section: A Choqueunclassified